Garden cities and suburbs in Brazil: recurrent adaptations of a concept - Rego, Renato (International Planning History Society Proceedings, 2016)
What is the contribution of the garden-city idea to urbanization in Brazil? Focusing on several layouts for new towns and suburbs designed along garden-city lines all over the country throughout the twentieth century, this paper will show that the garden-city idea was adapted to various purposes and different contexts and will present a panorama of recurrent adaptations. Planning ideas are not imported and put into use as easily as a material object. They rather involve emulation, rejection, combination, and transformation; a selective borrowing of the original idea also occurs, and some hybridization with other physical models might be observed. Indeed, the movement of ideas – from person to person, from situation to situation, from one period to another – necessarily involves processes of representation and institutionalization, which are different to those at their point of origin. More commonly, foreign cultural aspects are partially accommodated and transformed by their new uses and their position in a new time and place. With no specific association in Brazil, the garden city was soon locally disseminated through isolated personal attitudes and international intercourse. The role of model towns and native aspirations helped stimulate the mirroring of progressive ideas and modern practices, and the sophisticated way the garden-city image dealt with nature within the urban form suited different proposals and local interests. Thus, urban parks, abundant open spaces, and parkways were tools for building an uncommon urban beauty; the copious green areas and tree-lined streets not only created pleasant townscapes but also improved tropical urban climates, and the conformation of the urban settlement according to site conditions was a technical improvement. Moreover, along with low population density and larger lots, the irregular street layouts produced what were taken as a modern urban environment. The garden-city idea was also the conceptual basis for regional planning through the connection of town and country zones and the construction of city clusters; it was the root for the lay out of new capital cities, spa towns, and urban settlements in pioneering agricultural frontiers and colonization areas as in the Amazonia. Additionally, garden suburbs have been created for both the upper classes and workers, and in both cases were regularly related to ideas of good living and high quality of life. Occasionally, garden-city corollaries have also been merged with City Beautiful aspects, so irregularity and picturesqueness ended up being combined with vista, formality and classicism. As a conclusion, the paper will stress that the fashionable garden city was mostly and extensively used as a way of achieving modernity, a civilizing instrument, a real-estate venture, as well as an effective regional planning tool. It was adopted not because of effective urban-reform initiatives or genuine social problems; it was mainly embraced for stylistic convenience, ideological principles, and as a marketing strategy.